In Vitro And In Vivo Studies On The Complementary Effects Of Standardized Ethanolic Orthosiphon Stamineus Extract On Pancreatic Cancer Cells - Salem Yehya, Ashwaq Hamid (2018)
Pancreatic cancer is globally known as the fourth most lethal cancer in the world. Despite increasing understanding in tumor biology; the efficiency of treatment in pancreatic cancer remains challenging as patients demonstrate resistance to standard treatments. Although the first line agent, gemcitabine has produced clinical response to treat pancreatic cancer, the prognosis remains dismal.